2020
DOI: 10.1039/d0ee00723d
|View full text |Cite
|
Sign up to set email alerts
|

Dendrite-free Zn electrodeposition triggered by interatomic orbital hybridization of Zn and single vacancy carbon defects for aqueous Zn-based flow batteries

Abstract: Highly reversible aqueous zinc anodes are demonstrated via suppressing surface diffusion of Zn adatoms from strong orbital hybridization of the Zn adatoms and single vacancy defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(68 citation statements)
references
References 54 publications
1
67
0
Order By: Relevance
“…[ 29 ] Further studies on defective carbon hosts revealed defective zincophilic sites that can induce homogenous zinc plating. [ 34,35 ] Therefore, the strategy of tuning zincophilicity of the surface has been proposed to suppress zinc‐dendrite formation and boost electrochemical performance. [ 36–41 ] However, the detailed nucleation of zinc and the mechanism on zincophilic sites is not understood.…”
Section: Figurementioning
confidence: 99%
“…[ 29 ] Further studies on defective carbon hosts revealed defective zincophilic sites that can induce homogenous zinc plating. [ 34,35 ] Therefore, the strategy of tuning zincophilicity of the surface has been proposed to suppress zinc‐dendrite formation and boost electrochemical performance. [ 36–41 ] However, the detailed nucleation of zinc and the mechanism on zincophilic sites is not understood.…”
Section: Figurementioning
confidence: 99%
“…[8][9][10] Them ajor obstacle for developing advanced ZIBs with long cycle life lies in the suppression of Zn dendrite and byproducts derived from decomposition of active H 2 Om olecules belonging to solvation layer of Zn 2+ inside the electrolyte. [8] There are numerous strategies to alleviate or suppress the Zn dendrite under some mild test conditions,s uch as controlling oriented growth of specific crystal plane, [11,12] coating ap rotective layer on Zn surface, [13][14][15][16] depositing Zn nanostructure on 3D skeleton, [17][18][19][20] modulating electrolyte structure. [21][22][23][24][25][26][27][28] Mixing some additives (including solute or solvent) into the original electrolyte is asimple and affordable solution for restraining the growth of dendrite.…”
Section: Introductionmentioning
confidence: 99%
“…An umber of approaches have been reported to enhance Zn electrode reversibility including,b uilding artificial solid/ electrolyte interphases, [7] introducing an electrolyte additive, [8] modifying current collectors, [9] developing functional gel electrolyte, [10] and controlling Zn deposition. [11] Highly concentrated Zn-based electrolytes have recently been proposed for high-performance aqueous batteries. [6a, 12] By decreasing the number of free water molecules in the electrolyte,t he water-induced H 2 evolution and corrosion reaction were suppressed.…”
Section: Introductionmentioning
confidence: 99%